Arqueologia de uma sala de aula: práticas artísticas como campo experimental e crítico do ensino e da aprendizagem da arquitetura e do urbanismo - Feitosa, Ana Rosa Soares Negreiros (2023)
This paper reflects on the theory and practice of teaching architecture and urbanism in undergraduate courses, permeated by artistic practices as an experimental and critical field. Based on the assumptions and social responsibilities of architects and architecture teachers, it raises questions about how to make teaching/learning relevant to the contemporary problems of our field.And, effectively, what would be the place of the classroom in the process of shaping the body of knowledge of architects and urban planners?As in an archaeological study, some aspects of the classroom are revealed in layers, some of them are buried, but possible to be exposed,helping us to understand the founding cultural conformations, being instituted or imposed, as well as finding cracks, generating deconstructions and new compositions.Seeking to carry out a prospection, taking the ‘classroom’ as a training territory, a time-space for the possibility of experimentation, with the aim of understanding its place in the foundation processes of architecture and the knowledge processes.The research was triggered by the reflection on the meaning of the experiences carried out during the teaching of the Plastic Workshop discipline, inhabiting ‘Room 562’, between 2011 and 2019, at the Faculty of Architecture and Urbanism of the Federal University of Piauí. By using the documentation developed with the students, records of the meetings and activities of the didactic-pedagogical proposals, and carrying out a final collective artistic intervention, where a thousand photographs were developed and by fifty former students intervened, becoming another device for triggering memories, which helped the displacement of information and knowledge, resignifying a time-space, which crossed the walls of a cube room, and manifested the power of the territory. Philosophy, pedagogy, psychology and, above all, contemporary art, were fundamental axes, guiding lines for the methodological thinking and doing of this research. And finally, the comprehension of the classroomas a space made up of small and continuous practices where bodies learn to read verbal and non-verbal language, to interpret critically, and find meanings, significances of their own lives, and create new worlds for themselves and others,for this space is a reflection of our political choices, of the ways in which we govern educational and formative actions. The aim here is to broaden perspectives, where learning spaces involve the liberation and fullness of our existences.